THE EFFECT OF CHICKEN MANURE DOSE ON GROWTH AND YIELD OF BIG RED BEANS (Phaseolus vulgaris. L) - Widodo, R. Wahyono (Jurnal Pertanian, 2019)
Nutritional composition of large red beans (Phaseolus vulgaris L.) is good for health, much in demand by people for daily cooking, as raw material for making “dodol” or baby food, but production tends to decrease due to land conversion or soil degradation due to inorganic fertilization over do it. On the other hand, population growth continues to increase, demanding higher production. Fertilization of chicken manure can be expected to improve physical, chemical, and biological soil properties so that productivity increases.The study was conducted in the Tanjungsari SMK-PPN Field, Tanjungsari District, Sumedang Regency with a height of 850 m above sea level, Andisol soil order and type of rainfall C. The experiment was conducted from June to August 2018. The purpose of this study was to study the effect of chiken manure dosage on growth and yield of large red bean plants. The research method was a field experiment using a Randomized BlockDesign. The treatment in the form of dung manure consists of 5 levels (0, 10, 20, 30, and 40 tons ha-1) which are repeated five times.The experimental results show that the dose of chicken manure influences the plant height of 6 MST, number of leaves per plant 4 MST and 6 MST, number of pods per plant, number of seeds per plant, weight of wet seeds per plant, weight of dried seeds per plant, weight of 100 grains , and dry seed weight per plot, but no effect on other observations. The dosage of 40 tons ha-1 chicken manure gives the best dry beans weight per bean per plot even though it is not significantly different from the 30 tons ha-1 fertilizing chicken coop.